Using a Mathematical Model to Prepare a Budget for Specific Activities in Institutions - Hayder N Kadhim; Janaan A ALshamkhawii; Athraa N Albukhuttar (International Journal of Scientific Trends, 2023)
In this research, we found the possibility of calculating the budget of different activities for a particular institution by a mathematical model without relying on the initial costs of the activities and solving them using the Novel transformation.